ANALYSIS OF MANAGEMENT AND UTILIZATION OF CAPITATION FUND DENTISTS IN THE CITY OF PALEMBANG AND LUBUKLINGGAU - Faiznur Ridho; Bambang B. Soebyakto; Haerawati Idris (The Indonesian Journal of Public Health, 2020)
Primary dentists at the era of the National Health Insurance are only paid IDR2,000 each patient. The Capitation funds can not cover the cost of services that must be spent. The payment system must be improved because it is related to the quality of service. The aims of this study to analyze the management and utilization of  dental capitation funds including the bottlenecks and to generate solutions in the implementation of JKN. This research was descriptive with qualitative approach. The informants of the study were 16 (sixteen) dentists as an independent practitioners and pratama clinics in Palembang and Lubuklinggau with highest and lowest capitation coverage. Data were analyzed by data reduction, data presentation, conclusion drawing and verification. The result showed that there was a disparity in capitation fund income received by dentists both as an independent practitioners and pratama clinic. Not all dentists get the ideal number of participants 1: 10,000. Dentists with low capitation norms have difficulty to set their operational funds. The budget for operational cost is bigger than services cost. Revenues compared to capitation funds are still lacking. Most capitation funds for primary dentists are insufficient and still rely on fee for service patients. The government  should set dental capitation norm and regulation for National Health Insurance era.Key words: dentist, capitation, clinic, utilization, regulation